Pengembangan Pengelolaan Kas Negara di Indonesia Berdasarkan Best Practices Internasional: Sebuah Studi Komparasi - Marwanto Harjowiryono; Tri Angga Sigit (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2022)
Government cash management implementation in Indonesia adapts various international best practices. The cash management process starts comprehensively from implementing the Treasury Single Account until the Cash Optimization Activities to utilize idle cash both in the rough and fine-tuning phase. This study aims to compare the management of state treasury in Indonesia with France, the United States, Australia, Vietnam, , Philippines and South Africa. The research is conducted by a literature study method to examine written sources related to the implementation of cash management in those countries. The author compares the implementation of the Treasury Single Account aspect, the implementation of Cash Forecasting, Determination of Cash Buffer levels, and Cash Optimization Activities and provides recommendations in managing state treasury in Indonesia. Room for improvement in managing the state treasury in Indonesia includes expanding the application of the Treasury Single Account Up to Local Governments and BLUs, Implementation of Scheduled Payment Dates in increasing accuracy and automation of Cash Planning, Issuance of SPNs in less than three months to overcome Cash Mismatches and, Increasing TDR managed funds to commercial banks as well as increasing remuneration and the addition of term deposit instruments for the placement of government cash balances in Bank Indonesia.